2011
DOI: 10.4236/jbnb.2011.24055
|View full text |Cite
|
Sign up to set email alerts
|

<i>β</i>-cyclodextrin Covalently Functionalized Single-Walled Carbon Nanotubes: Synthesis, Characterization and a Sensitive Biosensor Platform

Abstract: In this study, we presented the preparation of β-cyclodextrin (β-CD) covalently functionalized single-walled carbon nanotubes (SWCNTs) and its application in modifying the solid glass carbon electrode (GCE). Cyclic voltammetry (CV) method was employed to evaluate the performance of the modified GCE. Solubility experiment indicated the conjugation of SWCNTs and β-CD, SWCNTs-β-CD with 8 wt% β-CD content could be well dispersed in water. High-resolution transmission electron microscopy (HRTEM) demonstrated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…As compared with the gold case, the number of reports of immobilization of CDs on carbon materials is not as high. However, some reports have shown that CDs can be either adsorbed on carbon-based nanomaterials having high surface area and high porosity as activated carbon (AC), 18 immobilized on the surface of carbon-coated cobalt nanomagnets, 19 covalently immovilized at single-walled carbon nanotubes 20 or electrochemically deposited as a film on carbon paste. 21 The grafting of native β-CDs has been also investigated using glutaraldehyde and 1,4-phenylene diisocyanate as organic linker molecules on AC, 22 however, this latter procedure is very time-consuming due to the many hours involved in the various steps of mixing.…”
mentioning
confidence: 99%
“…As compared with the gold case, the number of reports of immobilization of CDs on carbon materials is not as high. However, some reports have shown that CDs can be either adsorbed on carbon-based nanomaterials having high surface area and high porosity as activated carbon (AC), 18 immobilized on the surface of carbon-coated cobalt nanomagnets, 19 covalently immovilized at single-walled carbon nanotubes 20 or electrochemically deposited as a film on carbon paste. 21 The grafting of native β-CDs has been also investigated using glutaraldehyde and 1,4-phenylene diisocyanate as organic linker molecules on AC, 22 however, this latter procedure is very time-consuming due to the many hours involved in the various steps of mixing.…”
mentioning
confidence: 99%
“…8 This class of cyclic oligosaccharides consists of six, seven and eight glucopyranose units to form α-, βand γ-CD. 16 It is worth mentioning that, although some examples of CD coupled with nanomaterials have already been published, [17][18][19][20][21] no literature about NC decorated with CD has been reported until now. In particular, this type of macrocycle has been used in separation science [9][10][11][12][13][14] to distinguish enantiomers 15 based on the selective molecular interaction afforded by the CD cavities for trapping a target molecule from a complex matrix.…”
Section: Introductionmentioning
confidence: 99%
“…However, other applications such as the antibacterial activity of modified cellulose fibers with β-cyclodextrin have recently been published. 16 It is worth mentioning that, although some examples of CD coupled with nanomaterials have already been published, [17][18][19][20][21] no literature about NC decorated with CD has been reported until now.…”
Section: Introductionmentioning
confidence: 99%